Cognition in older adults with severe to profound sensorineural hearing loss compared to peers with normal hearing for age. (2nd April 2020) - Huber, Maria; Roesch, Sebastian; Pletzer, Belinda; Lukaschyk, Julia; Lesinski-Schiedat, Anke; Illg, Angelika
Abstract: Objective: Cognitive performance of older adults with severe to profound sensorineural hearing loss and indication for cochlear implantation was evaluated compared to peers with age appropriate hearing. Design: Prospective matched case control study. Study sample: Study group consisted of n = 30 patients aged between 60 and 80 years, with adult onset, severe to profound sensorineural hearing loss on both sides and indication for cochlear implantation. Matched control group consisted of n = 30 peers with age-adjusted hearing abilities, based on age- appropriate norms. Results: Differences in Constructional Praxis and Recall, Trail Making Test A and Stroop were not significant between both groups. However, the differences in Clock Drawing Test, Word Lists and Trail Making Test B were significant. The impairment in TMT B (cognitive flexibility) was mediated via the severity of depressive problems. Cognitive performance was not related to word recognition, the percentage and duration of hearing loss and hearing aid use. Conclusion: Severely hearing-impaired older adults show widespread impairments in cognitive performance.